Oportunidades para a prática de atividade física em escolas públicas e privadas de Curitiba, Brasil - Crisley Vanessa Prado; José Cazuza de Farias Júnior; Bruno Czestschuk; Adriano Akira Ferreira Hino; Rodrigo Siqueira Reis (Universidade Federal de Santa Catarina, 2018)
The school represents an space with opportunities for physical activity (PA) practice in children and adolescents. However, there is still limited evidence on local strategies, structures and policies for PA in the school environment in Brazil. The aim of the study was to identify PA opportunities in public and private schools in Curitiba, Brazil. A total of one hundred sixty one schools were identified from a household survey conducted with adolescents from Curitiba, Brazil from which 107 (72.6% publics) participated in this study. One physical education teacher from each participant school was interviewed. Nearly all schools offered two weekly PE classes (97.1%), lengthing 45 to 50 minutes (95.7%). PE annual training was more frequent among public schools (92.9%). Most schools offered one recess interval (92.3%). However, recess interval of 16-30 minutes (75.0%), supervised (65.6%) and with PA equipment (65.6%) were more frequent among private schools. After school activities were offered in eight out of ten schools, and PA opportunities in other contexts were more frequent in private schools (40.0% vs. 14.3%, p = 0.003). However, more public schools participated in state sponsored programs (57.6% versus 31.2%, p = 0.011). Opportunities for PA in the investigated schools is offering by insufficient frequency and length for promoting PA at the recommended levels in this context.